Reconstruction from the aspects of Islamic law in corporate zakat accounting - Irfan Irfan; Muhyarsyah Muhyarsyah; Arif Pratama Marpaung; Ina Liswanty (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2020)
This research aims to explore the concept of corporate zakat accounting from the aspects of Islamic law as the basis to determine muzakki (zakat payer) and legally mandate companies to pay zakat. This is a qualitative research with the data obtained through a literature study by exploring various classical and contemporary sources using historical, analytical, and critical tools. The research also examined the concepts of fiqh and sharia in economic activities. This paper found that companies were synonymous to syirkah in terms of a spiritual entity with the inherent traits in humans as the right to accept and fulfil the responsibilities. Consequently, companies are mandated to pay zakat based on the five principles of muzakki with the calculations carried out using the corporate zakat accounting method based on the established standards. This process positively assists companies in the realization of a fair and equitable distribution of wealth, as well as in the emergence of corporate social responsibility collectively and individually.